Abu Hamid al-Ghazali in Our Times: How al-Ghazali is Interpreted and Transmitted in the Contemporary Turkish Context - Bacik, Gokhan (Tashwirul Afkar, 2023)
Whether Abu Hamid al-Ghazali contributed to the decline of rationalist and scientific tradition in the Muslim world is a grand debate in Islamic studies. However, the literature on this question ventures only to construct a historical debate. Though al-Ghazali died in 1111, his opinions still influence Muslims today. So this research, rather than contribute to that historical debate, studies how al-Ghazali is interpreted in contemporary Turkey, and what this interpretation reveals about approaches to natural law, knowledge and philosophy (essentially, the study of conceptual lucidity and the valid procedures of reasoning). These three disciplines are chosen because al-Ghazali is accused of contributing to the decline of the scientific tradition in the Islamic world because of his criticism of philosophy, his occasionalist view of causality, and his incorporation of inner knowledge into Sunnism. The research aims to answer questions like: ‘Are al-Ghazali’s works referenced today to justify a hostile stance on philosophy?’ To achieve this goal, the research studies how al-Ghazali is interpreted by two Islamic social movements in Turkey: Işıkçılar and Erenköy. Studying these cases, the paper concludes that how al-Ghazali is interpreted and transmitted in Turkey contributes to (i) a highly sceptical stance on natural law, (ii) a deep suspicion of rational knowledge and the consequent belief in inner knowledge, and (iii) a highly critical stance on philosophy.